2018
DOI: 10.1016/j.fct.2018.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis induction by Pleurotus sajor-caju (Fr.) Singer extracts on colorectal cancer cell lines

Abstract: Pleurotus sajor-caju (PSC) is an edible mushroom used in food supplements, presenting antitumor properties through induction of cell death pathways. The PSC potential against colorectal cancer was analyzed by exposing HCT116 cells to different PSC extracts. The PSC n-hexane extract (PSC-hex) showed the highest cytotoxicity effect (IC value 0.05 mg/mL). The observed cytotoxicity was then associated to apoptosis-promoting and cell cycle-arrest pathways. PSC-hex was able to induce apoptosis related to breakdown o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…Such an effect may be related to the higher level of phenolic compounds and the higher CAT and SOD activity. Similar effects of Lentinula edodes and Lentinus sajor-caju on HEp-2 and HeLa (cervical cancer) and L. sajor-caju on HeLa and HepG2 (hepatocellular cancer) were demonstrated by Finimundy et al [47,48]. In another study conducted by Seedevi et al, free radical scavenging activity was exhibited by polysaccharide isolated from L. sajor-caju [49].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Such an effect may be related to the higher level of phenolic compounds and the higher CAT and SOD activity. Similar effects of Lentinula edodes and Lentinus sajor-caju on HEp-2 and HeLa (cervical cancer) and L. sajor-caju on HeLa and HepG2 (hepatocellular cancer) were demonstrated by Finimundy et al [47,48]. In another study conducted by Seedevi et al, free radical scavenging activity was exhibited by polysaccharide isolated from L. sajor-caju [49].…”
Section: Discussionsupporting
confidence: 54%
“…Chaturvedi et al reported similar results revealing cytotoxic and pro-apoptotic effects of PSC water extract on HCT-116 cells [51]. The fungus was studied on other models, as well, and was shown to affect human cervical cancer HEp-2 and HeLa cells [47], breast cancer MCF-7 and non-small cell lung cancer NCI-H460 cells [48], and human gastric cancer (AGS) and hepatocellular carcinoma cells (HepG2) [49]. Many more mushrooms and derived compounds have been demonstrated to possess anti-cancer activity.…”
Section: Discussionmentioning
confidence: 79%
“…Finimundy et al investigated the antitumor, specifically cell-death-inducing properties of P. sajor-caju on colorectal cancer model [147]. Pleurotus sajor-caju fruiting bodies extracts were obtained using various solvents [n-hexane, chloroform, ethyl acetate, ethanol and ethanol/water (1:1, v/v)].…”
Section: Genus Pleurotusmentioning
confidence: 99%
“…Singer extracts. 45 Screening of the Potential Antitumor Activity of Pleurotus ostreatus Phenolic Compounds This study was focused to predict putative mechanisms of action of phenolic compounds occurring in P. ostreatus, those with significant Tanimoto's coefficient, since it would correspond to structurally similar molecules that present high probability to show a similitude in their biological activities. Twenty antitumor reference compounds showed structural similarity to 3 phenols occurring in P. ostreatus: protocatechuic acid, and the flavonoids myricetin and naringin.…”
Section: Screening Of Phenolic Compounds With Potential Regulatory Efmentioning
confidence: 99%